Developing business process analyst competencies through higher education institution interventions - a Kenyan study - Wamicha, Elizabeth (Department of Information Systems, 2019)
Kenya is currently experiencing large-scale economic growth. With this economic growth has come the need for organizations to have well-defined business processes largely through the development of business process management (BPM) initiatives. There is also an increasing move towards the automation of these business processes mainly through the implementation of enterprise resource planning (ERP) systems. This has given rise to the need for business process analyst (BPA) role. BPAs are essential to driving both BPM initiatives and ERP systems implementations. Given this scenario, the first motivation for this study was to investigate the status of BPM in Kenya and the role of the BPA in organizations in Kenya. This study specifically investigated BPA competency-building interventions required to drive BPM maturity and ERP systems implementation projects. Given that no BPM curriculum existed in Higher Education Institutions (HEI) in Kenya at the commencement of this study, the second motivation of the study was to investigate how these BPA competency-building interventions could be adapted into BPM curriculum. To answer the research questions for this study, the pragmatic research paradigm was used. A hybrid inductive-deductive research approach was deemed most appropriate. This study used a mixed methods approach. This meant that both quantitative and qualitative data was collected. Data for this study was collected iteratively between March 2016 and October 2018 using a crosssectional or multiple snapshots time horizon. Results from the data analysis explained 12 BPA competency-building interventions. Thereafter, a BPM curriculum was designed using the design science research method (DSRM). The study incorporated the concepts of the 4I framework of organizational learning and the concepts of the activity system. The scientific contributions of this study comprise three aspects. Firstly, this research identified that certain BPA competencies such as business requirements elicitation, business process improvement, business analysis and holistic overview of business thinking were perceived to have been undervalued in the Kenyan context. Business process orchestration competencies were perceived to be critical for driving BPM in organizations and for successfully managing ERP systems implementations. Secondly, the study established that BPA competency-building interventions such as inter-group collaboration, on-the-job/experiential learning and vendor certifications were among the highly impactful interventions. Thirdly, the study designed a novel BPM curriculum, a first for Kenya. The curriculum incorporated the 4I framework of organizational learning and activity systems in its design and implementation. The results of the evaluation of the BPM curriculum established that students found it useful for building critical BPA competencies such as business analysis, business requirements elicitation and business process improvement. Data collection for this study was limited to the BPA role within organizations and Business and Information Technology students undertaking a BPM course in HEI within the Kenyan context. Future research can extend data collection to other key staff members such as managers and human resource experts. Further, the BPM curriculum artefact was evaluated in the last 2 weeks of a 4-month semester within which the BPM curriculum was run. Therefore, a comprehensive evaluation could not be carried out due to time constraints. Future studies can extend findings from this study by using a design science approach of artefact evaluation to implement a comprehensive and detailed evaluation of the BPM curriculum. This can provide additional insights into the ways in which the BPM curriculum can be improved. There is also an opportunity to use action research as a methodology to validate the educational interventions established in this study. Action research would drive in-depth engagement with both BPAs in industry and students undertaking BPM curriculum in HEI with the aim of effecting contributions to both theory and practice.